Christmas after all : the Great Depression diary of Minnie Swift - Lasky, Kathryn (New York : Scholastic, 2001)
In her fictionalized journal, eleven-year-old Minnie Swift recounts how her family dealt with the difficult times during the Depression and how the arrival of an orphan from Texas changed their lives in Indianapolis just before Christmas 1932.
"Indianapolis, Indiana, 1932"--Cover.
770
Accelerated Reader AR
Keywords: Depressions -- 1929 -- Juvenile fiction; Families -- Juvenile fiction; Orphans -- Juvenile fiction; Diaries -- Juvenile fiction; Christmas stories; Depressions -- 1929 -- Fiction; Family life -- Indiana -- Fiction; Orphans -- Fiction; Diaries -- Fiction; Indiana -- Juvenile fiction; Indiana -- Fiction